Towards a framework of relationship marketing; An initial case study - Peck, Helen (Cranfield School of Management, 1997)
Abstract: The reshaping of organisations towards flatter, more responsive network forms and the rise of relationship marketing are related, not as cause and effect, but as part of the same phenomena. They are responses to environmental turbulence and the pursuit of a common goal - the creation of competitive advantage in a changing world. Whether organisational changes are overtly marketing driven or not, marketing's role within these new functionally disaggregated organisations is being transformed. There is now a growing consensus among marketing scholars that marketing's new remit extends well beyond the dyadic relationship between an organisation and its customers, though as yet there is little consensus beyond this point. There are however calls from academics and practitioners alike, for effective new frameworks which conceptualise the scope, properties and remit of relationship marketing at the organisational level. While some writers have endeavored to provide such frameworks, drawing from anecdotal evidence and plausible theory borrowed from related fields, as yet these frameworks appear to be empirically untested. The aim of this paper is to present a case study of Laura Ashley Holdings Plc, undertaken to assess of an existing, but empirically untested conceptual framework for relationship marketing. The case study represents the first or `initial' case study, within a wider retroductive research strategy, undertaken in the Realist research tradition, using a multiple embedded case study research design. It was undertaken as part of an on-going doctoral research project, the aim of which is to develop an empirically robust and theoretically grounded framework of relationship marketing at the organisational level. This paper describes in some detail the processes and methods used for data collection, analysis and vertification stages of the case study. These are presented together with a summary of the findings and preliminary suggestions for the development of a new framework of relationship marketing.